Engajamento e ambientes virtuais imersivos: uma proposta de diretrizes - Carvalho, Aderson de (2018)
In view of the difficulty in student involvement and the constant search for enveloping technological educational resources, this study aimed at developing guidelines for the development of immersive virtual environments. To do so, the methodological steps used were data collection from the Theory of Engagement; Professional opinion and experiment with students; compilation of data and elaboration of the guidelines; validation and application. In this way, it was possible to identify 15 guidelines whose characteristics point to the best practices to foster engagement within surrounding virtual environments (according to the data collected). Therefore, the evaluation was performed through a virtual questionnaire and sent to professionals in the area of Information Technology of the Federal University of Santa Maria and Federal University of Rio Grande do Sul. The research universe comprised eight responses. In this way, the questionnaire was the methodological tool that guided this evaluation, and its elaboration aimed to measure issues related to utility, adequacy and clarity. Finally, validation resulted in an overall average score of 6.35 / 7.00. In this context, it can be concluded that the set of guidelines represents a relevant instrument to assist designers and developers of Immersive Virtual Environments.